Peningkatan Kinerja Sumber Daya Manusia Dengan Memberi Motivasi dan Disiplin - Lia Nuraeni; Eman Sulaeman (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is to analyze the influence of motivation, employee involvement and organizational culture on staff performance. The Central Java Provincial Cooperative Micro-SME Office has an important role and task in the formation or leadership of small and medium-sized micro-cooperatives, the scope of factors that can improve the efficiency of human resources in carrying out their tasks must be looked at 162 officials of small and medium-sized cooperatives in Central Java Province participated in this study, and 110 respondents participated in this study. The analysis results using multiple linear regression showed that motivation has a positive effect on organizational commitment and improving employee performance, and commitment has a positive effect on improving staff and applying the influence of organizational culture to moderate the current structure to achieve staff improvement. performance of resources.